2015
DOI: 10.31186/jagrisep.14.1.1-10
|View full text |Cite
|
Sign up to set email alerts
|

STRATEGI PENGEMBANGAN PALA (Myristica fragan haitt) DI KECAMATAN TANJUNG RAYA KABUPATEN AGAM (Studi kasus : Kelompok Tani Sabik Tajam Nagari Tanjung Sani)

Abstract: The study aims to analyze development strategy of nutmeg (Myristic fragan haitt) in Tanjung Raya Sub-district, Agam District. The study applied decriptive method. The data were collected through in depth interview with three internal key infromants, in this case farmers, and external key informants including head of forestry and plantation department of Agam District, and one nutmeg farmer. SWOT analysis were applied to formulate development strategy of nutmeg at Sabik Tajam farmers group in Tanjung Raya Sub-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
1
0
6
Order By: Relevance
“…The methods using in this steps was made the Internal-External Matrix to formulating the strategies. In this matrix IFE parameters inputing to horizontal axis (X) and EFE to the vertical (Y) (Analia, 2015;Badrudin et al, 2017) matrix separated to 3 parts indicated various specific strategy of each parts. 1th part at I, II and IV cell describe as growt and build with the choice strategy: "market development" and "products development" as suitable strategies.…”
Section: Matching Of Ife and Efementioning
confidence: 99%
“…The methods using in this steps was made the Internal-External Matrix to formulating the strategies. In this matrix IFE parameters inputing to horizontal axis (X) and EFE to the vertical (Y) (Analia, 2015;Badrudin et al, 2017) matrix separated to 3 parts indicated various specific strategy of each parts. 1th part at I, II and IV cell describe as growt and build with the choice strategy: "market development" and "products development" as suitable strategies.…”
Section: Matching Of Ife and Efementioning
confidence: 99%
“…Indonesia cukup diperhitungkan di dunia internasional karena merupakan salah satu negara penghasil rempah-rempah. Salah satu rempah-rempah yang asli berasal dari Indonesia adalah pala tanaman (Analia, 2015).…”
Section: Pendahuluanunclassified
“…Indonesia kaya akan tanaman perkebunan yang bernilai tinggi dan mampu bersaing di pasar dunia. Rempah-rempah merupakan salah satu jenis tanaman yang berpotensi untuk diperdagangkan dan cukup diperhitungkan di perdagangan internasional (Analia, 2018). Salah satu rempah yang berasal dari Indonesia adalah Pala.…”
Section: Pendahuluanunclassified
“…Biji dan fuli (bunga) pada buah pala dapat dijadikan sebagai minyak. Sedangkan daging buah pala dapat dimanfaatkan untuk diolah menjadi manisan, asinan, dodol, selai, dan sirup (Analia, 2018).…”
Section: Pendahuluanunclassified